THE INFLUENCE OF OWNERSHIP STRUCTURE ON FINANCIAL PERFORMANCE OF GASOLINE FIRMS - Thu, Nguyen Van; Luan, Nguyen Van; Anh, Cao Thi; Tri, Nguyen Van; Bac, Dang Thi (Veredas do Direito, 2026)
The purpose of this research is to investigate the impact of Foreign Ownership (FO), Organizational Ownership (IO), Internal Ownership (MO), Ownership Concentration (OC), and State-Owned (SO) on financial performance, measured by return on assets (ROA), of gasoline enterprises on the Vietnamese stock market. The research sample consists of 20 listed gasoline firms observed over the period 2021–2024, employing a combination of qualitative and quantitative research methods. A regression model is developed to examine the relationships between the explanatory variables and ROA, while ensuring the validity of key linear regression assumptions. The empirical results reveal that no effect of organizational ownership (IO) on ROA was found; no effect of foreign ownership (FO) on ROA was found; internal ownership (MO) had a negative effect with a coefficient of -.0818785; ownership concentration (OC) had a positive effect with a coefficient of .0432445; and state-owned (SO) had a negative effect with a coefficient of -.0423326. The findings provide valuable empirical evidence for corporate managers, investors, and policymakers in designing financial strategies and improving the business performance of gasoline enterprises in Vietnam.